2003
DOI: 10.1088/0305-4470/36/30/307
|View full text |Cite
|
Sign up to set email alerts
|

Nonconservative Lagrangian mechanics: a generalized function approach

Abstract: We reexamine the problem of having nonconservative equations of motion arise from the use of a variational principle. In particular, a formalism is developed that allows the inclusion of fractional derivatives. This is done within the Lagrangian framework by treating the action as a Volterra series. It is then possible to derive two equations of motion, one of these is an advanced equation and the other is retarded.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 10 publications
0
78
0
Order By: Relevance
“…Neither Riewe [9,10] nor Dreisigmeyer and Young [6] were able to remove RFDs completely. Riewe suggested replacing RFDs with LFDs in the resulting equations of motion.…”
Section: Fractional Derivativesmentioning
confidence: 95%
See 3 more Smart Citations
“…Neither Riewe [9,10] nor Dreisigmeyer and Young [6] were able to remove RFDs completely. Riewe suggested replacing RFDs with LFDs in the resulting equations of motion.…”
Section: Fractional Derivativesmentioning
confidence: 95%
“…In examining Riewe's approach, Dreisigmeyer and Young showed that his procedure of replacing anti-causal with causal operations may not be a wise idea [6]. While still employing fractional derivatives, Dreisigmeyer and Young instead allowed for a causal equation and an anti-causal dual equation to arise.…”
Section: Corollary 11 the Equations Of Motion Of A Dissipative Lineamentioning
confidence: 99%
See 2 more Smart Citations
“…Many results have been published with concrete problems solved in classical spaces of functions and in the spaces of generalized functions. We cite only some of them, recently published or with a new approach: [2]- [4], [7], [8], [13], [15], [17], [19], [20], [22], [23] and with Karamata's regularly varying functions: [11], [24]. In this paper we treat such an equation with the boundary condition y(0) = y(b) = 0 in the space L 1 (0, b) and in a subspace of tempered distributions constructed for this problem.…”
Section: Introductionmentioning
confidence: 99%